2021
DOI: 10.1101/2021.05.14.444268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific bacterial cell wall components influence the stability of Coxsackievirus B3

Abstract: Enteric viruses infect the mammalian gastrointestinal tract and lead to significant morbidity and mortality worldwide. Data indicate that enteric viruses can utilize intestinal bacteria to promote viral replication and pathogenesis. However, the precise interactions between enteric viruses and bacteria are unknown. Here we examined the interaction between bacteria and Coxsackievirus B3, an enteric virus from the picornavirus family. We found that bacteria enhance the infectivity of Coxsackievirus B3 (CVB3) in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Recent data show intestinal bacteria can influence the intestinal replication of enteric viruses, including CVB3 (59-61). Our lab recently demonstrated that specific intestinal bacteria in male mice promote CVB3 infectivity and viral stability (62). While the mechanism is unclear for CVB3, a similar enterovirus, poliovirus, has been found to use bacteria to enhance attachment to the poliovirus receptor (63).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show intestinal bacteria can influence the intestinal replication of enteric viruses, including CVB3 (59-61). Our lab recently demonstrated that specific intestinal bacteria in male mice promote CVB3 infectivity and viral stability (62). While the mechanism is unclear for CVB3, a similar enterovirus, poliovirus, has been found to use bacteria to enhance attachment to the poliovirus receptor (63).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data also show that intestinal bacteria can influence the intestinal replication of enteric viruses, including CVB3 (48)(49)(50). We have recently demonstrated that specific intestinal bacteria in male mice play a role in promoting CVB3 infectivity and viral stability (51). While the mechanism is unclear for CVB3, a similar enterovirus, poliovirus, has been found to use bacteria to enhance attachment to the poliovirus receptor (49,52).…”
Section: Discussionmentioning
confidence: 98%